The macro-economic impact of changing the rate of corporation tax - Thomas Conefrey; John D. FitzGerald (The Economic and Social Research Institute (ESRI), 2009)
This paper considers the impact of changes in the rate of corporation tax in Ireland affecting the services sector. A model is estimated that relates services exports and output to world activity, competitiveness and the rate of corporation tax. This model indicates that a reduction in the rate of corporation tax in the 1990s stimulated exports and, even allowing for profit repatriations by foreign firms and replacement of lost tax revenue, it resulted in an increase in domestic output. The increase in profitability suggests that some of the increased output involved relocation of profits to Ireland by multinational firms.
Keywords: F2; H25; 330; corporation tax; Ireland; services sector; Unternehmensbesteuerung; Steuerreform; Wettbewerb; Dienstleistungssektor; Internationaler Dienstleistungsverkehr; Wirtschaftswachstum; Irland